Fundamentals of corporate finance - Brealey, Richard A. (McGraw-Hill, 1999)
In the first edition, Brealey, Myers, Marcus were applauded for their intuitive approach and imbedded examples. Professors constantly praised their well-organized and thoughtful writing style and their clear exposition of what many students consider difficult material. The authors accomplished this without sacrificing an up-to-date, technically correct treatment of core topic areas. Since this author team is known for their outstanding research, teaching efforts, and market leading finance textbooks, it's no surprise that they have created an innovative, modern, and market-driven revision.